Analytical model on the bond stress-slip relationship between steel reinforcement and concrete for RC beam-column joints - Long, Xu (2013)
There are no conventionally accepted failure criteria for progressive collapse, and often times, deflection of affected beams over the “missing column” are often used as performance criteria. However, when simulating the deformation behaviour and the strength of reinforced concrete (RC) framed structures for progressive collapse analysis, besides the flexural deformations, the so-called “fixed end” rotation induced by the longitudinal bar slip at the beam-column ends connected to the joints can be significant and result in additional lateral deformations not accounted for in the initial analysis. Hence, it is important to quantify the deformations arising from fixed end rotations. Several bond stress-slip relationships between steel reinforcement and concrete were previously proposed in the literature. In the present work, their merits and demerits are discussed in terms of application limitation. To address the limitations of previous bond-slip models, a new analytical model based on the bond stress integration along the bar stress propagation length is proposed to predict the bar-slip behaviour in the RC beam-column joints. The proposed analytical model on the bond stress-slip relationship is validated against experimental studies from the literature and is shown to be simple and reliable.